Non-recurrent inferior laryngeal nerve: a case report - Manish, Shah Urvin; Subbarayan, Boopathi; Subbaraj, Saravanakumar; Tirougnanassambandamourty, Tirou Aroul; Smile, S. Robinson (International Surgery Journal, 2020)
The incidence of Non-recurrent laryngeal nerve (NRLN) is reported to be 0.6%-0.8% on the right side and in 0.004% on the left side. Damage to this nerve during thyroidectomy may lead to vocal cord complications and should therefore be prevented. A middle-aged woman with a nodular goiter who underwent subtotal thyroidectomy for multinodular colloid goiter. We encountered a non-recurrent laryngeal nerve on the right side in a patient during surgery. We were not able to find the inferior laryngeal nerve in its usual position using the customary anatomical landmarks. Instead, it was emerging directly from the right vagus nerve at a right angle and entering the larynx as a unique non-bifurcating nerve. Nonrecurrent inferior laryngeal nerve incidence is very rare, but when present, increases the risk of damage during thyroidectomy. Hence, it is very important to be aware of the anatomical variations of the inguinal lymph node (ILN) and the use of safe meticulous dissection while looking for the nerve during thyroidectomy. The use of Intra-operative neuro-monitoring (IONM) if available in thyroid surgery allows the surgeon to recognize and differentiate branches of the inferior laryngeal nerve (ILN) from sympathetic anastomoses, as well as NRLN during surgery.